Effects of Rhizophora mangle on Experimental Colitis Induced by TNBS in Rats - de Faria, Felipe Meira; Luiz-Ferreira, Anderson; Rabelo Socca, Eduardo Augusto; Alves de Almeida, Ana Cristina; Dunder, Ricardo Jose; Manzo, Luis Paulo; da Silva, Marcelo Aparecido [UNESP]; Vilegas, Wagner [UNESP]; Rozza, Ariane Leite [UNESP]; Pellizzon, Claudia Helena [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Monteiro Souza Brito, Alba Regina (Hindawi Publishing Corporation, 2012)
Male Unib-WH rats were pretreated for two weeks with butanolic (BuOH) and ethyl acetate (EtOAc) fractions. Colitis was induced by rectal administration of TNBS, the treatment continued, and animals were sacrificed on day 7 after the TNBS administration. Phytochemical studies were performed in order to provide the characterization of the tannins present in the bark of R. mangle. Results showed that EtOAc fraction increased the levels of IL-10 (** P < 0.01) and diminished the levels of TNF-alpha (*** P < 0.001) and IL-6 (** P < 0.01). BuOH fraction reduced the MPO activity (** P < 0.01) and levels of TBARS (*** P < 0.001); it also increased COX-1 expression, diminished the levels of TNF-alpha (*** P < 0.001), and increased the levels of IL-12 (*** P < 0.001). Besides, both treatments augmented the levels of GSH (* P < 0.05), the activity of GSH-Px (** P < 0.01 for BuOH fraction and *** P < 0.001 for EtOAc fraction), and CAT (** P < 0.01). In conclusion, both treatments ameliorated the injury induced by TNBS through different mechanisms, probably by their chemical composition which directed its activity into an antioxidant or anti-inflammatory response, leading to an immune modulation.